Quantitative Analysis Towards Higher Order Thinking Skills of Chemistry Multiple Choice Questions for University Admission - Muhammad Reza*; Kana Puspita; Coryna Oktaviani (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
The research about quantitative analysis towards higher order thinking skill of chemistry multiple questions for university admission is carried out in the acceleration class of SMAN Modal Bangsa. This research aims to analyze the test of validity, reliability, correlation between difficulty index and discriminatory power, functioning and nonfunctioning distractors of chemistry multiple questions quantitatively which are frequently offered to students in national university admission. It used a descriptive-quantitative method and purposive sampling technique. Students of the acceleration class were selected purposely because they have been frequently answering the higher order thinking questions. Data were collected using 20 multiple choice questions developed from questions banks. Before questions used for students, the questions were assessed by two validators. The result of the validity test shows that 100% questions were valid with an average scale score of 0.93 (best valid). Further analysis used a reliability test to indicate the correlation of item score and total score of questions symbolized by Cronbach alpha of 0.94, 0.92 and 0.89 for aspect of content, construction, language or culture, respectively. The correlation between difficulty index and discriminatory power was reliable with correlation coefficient of 0.842. The final analysis is done towards distractor function, and it shows that overall 83.75% was functioning distractors. Then, nine questions or 45% met ideal expectations with four functioning distractors. Therefore, the most higher order thinking chemistry multiple questions have good quality or feasible to be used in university admission.    Keywords: higher order thinking, validity, reliability, difficulty index, discriminatory power and distractors